A reassessment of genetic diversity in Icelanders: strong evidence from multiple loci for relative homogeneity caused by genetic drift. - Helgason, A; Nicholson, G; Stefánsson, K; Donnelly, P (2003)
There has been some controversy in the literature concerning whether Icelanders are genetically homogenous or heterogeneous relative to other European populations. We reassess this question in the light of large data sets spanning 83 autosomal SNP loci, 14 serogenetic loci, 6622 Y-chromosomes and 3214 sequences from mtDNA hypervariable segments 1 and 2 (HVS1 and HVS2). Our results strongly support the hypothesis that genetic drift, with a consequent loss of variation, has had a greater impact on Icelanders than most other Europeans. We also analyse 7245 HVS1 sequences from 25 European populations. In line with other studies, we observe a deficit of rare HVS1 haplotypes and an excess of intermediate frequency haplotypes in Icelanders compared to most European populations, with some measures of genetic diversity indicating relative heterogeneity and others indicating relative homogeneity of Icelanders. Simulations indicate that genetic drift, and not admixture (as proposed by Arnason, 2003) is the most likely cause of the atypical Icelandic HVS1 frequency spectrum. These simulations reveal that gene diversity (heterozygosity) and mean pairwise differences are largely insensitive to events in recent population history, while statistics based on the number of haplotypes or segregating sites are much more sensitive. Overall, our analyses strongly indicate that the Icelandic gene pool is less heterogeneous than those of most other European populations.